Effectiveness and Safety of Concurrent Use of First-Line Antiretroviral and Antituberculous Drugs in Rwanda - Justin Ntokamunda Kadima; Marie Françoise Mukanyangezi; Claude Bernard Uwizeye (Journal of Tropical Medicine)
Background. Overlapping toxicity between drugs used for HIV and TB could complicate the management of HIV/TB coinfected patients, particularly those carrying multiple opportunistic infections. This study aimed to evaluate the clinical outcomes and adverse drug events in HIV patients managed with first-line antiretroviral and first-line anti-TB drugs. Methods. This is a retrospective study utilizing medical dossiers from single-HIV infected and HIV/TB coinfected patients already initiated on ART. Predictors of outcomes included changes in CD4 cells/mm3, body weight, physical improvement, death rate, and adverse drug reactions. Results. Records from 60 HIV patients and 60 HIV/TB patients aged between 20 and 58 years showed that all clinical indicators of effectiveness were better in single-HIV infected than in HIV/TB coinfected patients: higher CD4 cell counts, better physical improvement, and low prevalence of adverse drug events. The most frequently prescribed regimen was TDF/3TC/EFV+RHZE. The mortality rate was 20% in HIV/TB patients compared to 8.3% in the single-HIV group. Conclusion. Treatment regimens applied are efficient in controlling the progression of the infection. However, attention should be paid to adjust dosing when combining nonnucleoside antiretrovirals (EFV and NVR) with anti-TB drugs to minimize the risk of death by drug intoxication.